1980
DOI: 10.1128/aac.17.3.474
|View full text |Cite
|
Sign up to set email alerts
|

Activity of cefotaxime-aminoglycoside combinations against aminoglycoside-resistant Pseudomonas

Abstract: The activity of cefotaxime, either alone or combined with an aminoglycoside, was determined against 50 isolates of Pseudomonas aeruginosa, of which 50, 33, and 10 were resistant to gentamicin, tobramycin, and amikacin, respectively. Cefotaxime inhibited 34 isolates at a concentration of 16 ,ug/ml and all isolates at 128 ug/ml.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1981
1981
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…In a killing-curve study by Klastersky et al [13], the combination cefazolin and ami kacin acted synergistically against 75% of the investigated Klebsiella strains. In checkerboard studies of P. aeruginosa, ce fotaxime and gentamicin acted synergisti cally against approximately 60% of the strains [25,26]. This was in accordance with the 50% synergistic activity observed in our study when optimal concentrations of cefotaxime and netilmicin were tested.…”
Section: Discussionsupporting
confidence: 75%
“…In a killing-curve study by Klastersky et al [13], the combination cefazolin and ami kacin acted synergistically against 75% of the investigated Klebsiella strains. In checkerboard studies of P. aeruginosa, ce fotaxime and gentamicin acted synergisti cally against approximately 60% of the strains [25,26]. This was in accordance with the 50% synergistic activity observed in our study when optimal concentrations of cefotaxime and netilmicin were tested.…”
Section: Discussionsupporting
confidence: 75%
“…Due to the serious side effects of treatment with CHL, such as aplastic anemia [ 13 ], in the current study, we went on to evaluate the interaction between CTX and GEN, which inhibits protein synthesis by binding to the 30S ribosomal subunit instead of the 50S subunit as CHL does. This antibiotic was chosen instead of CHL because combination treatment between ß-lactams and aminoglycosides is well known and due to the fact that GEN is more relevant in human medicine [ 50 , 51 , 52 , 53 ]. Our results showed that the MIC of CTX could be reduced from 256 to 2 mg/L by the addition of just 0.5 mg/L GEN in E. coli MG1655 expressing bla CTX-M-1 .…”
Section: Discussionmentioning
confidence: 99%
“…Cephalosporins and penicillins are used frequently in combination with aminoglycoside antibiotics in the treatment of gram-negative rod bacteremia (4), and the synergistic activity obtained with these combinations has been related to improved outcome in severely neutropenic bacteremic patients (6). Also, in vitro studies have demonstrated synergism between cefotaxime and aminoglycosides against aminoglycoside-resistant strains of P. aeruginosa (8) Serum levels of moxalactam and cefotaxime were similar when the drug was administered alone or in combination with tobramycin. Cefotaxime levels at 1 h were 7.77 ± 1.2 tig/ml alone and 8.97 ± 1.5 tg/ml in combination.…”
Section: Moxalactam (1-oxa-/l-lactam) and Cefotaximementioning
confidence: 99%